2019
DOI: 10.4081/mrm.2018.104
|View full text |Cite
|
Sign up to set email alerts
|

The patient needing prolonged mechanical ventilation: a narrative review

Abstract: Background: Progress in management has improved hospital mortality of patients admitted to the intensive care units, but also the prevalence of those patients needing weaning from prolonged mechanical ventilation, and of ventilator assisted individuals. The result is a number of difficult clinical and organizational problems for patients, caregivers and health services, as well as high human and financial resources consumption, despite poor long-term outcomes. An effort should be made t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 47 publications
(53 reference statements)
1
21
0
Order By: Relevance
“…2 Muscle weakness is a major contributing factor, together with malnutrition, chronic cardiac and respiratory disease, depression, anxiety, and previous delirium. 19 Studies have suggested that a comprehensive rehabilitation strategy is desirable to facilitate the weaning program. 28 Our 15-y analysis yielded 3 main findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Muscle weakness is a major contributing factor, together with malnutrition, chronic cardiac and respiratory disease, depression, anxiety, and previous delirium. 19 Studies have suggested that a comprehensive rehabilitation strategy is desirable to facilitate the weaning program. 28 Our 15-y analysis yielded 3 main findings.…”
Section: Discussionmentioning
confidence: 99%
“…12 Evidence of benefits from early mobilization and physiotherapy has expanded through randomized, controlled trials and systematic reviews. [13][14][15][16][17][18][19] Accordingly, we conducted an analysis of all subjects admitted to our weaning unit over a 15-y period who were on prolonged mechanical ventilation and underwent an intensive physiotherapy program. We assessed the effect of the physiotherapy program on the weaning success rate, as well as the correlates of weaning success and changes in outcomes over time.…”
Section: See the Related Editorial On Page 112mentioning
confidence: 99%
“…− Twice per day evaluation of respiratory clinical parameters (temperature, SpO 2 , SpO 2 /FiO 2 , cough, dyspnea, manual muscle test, isokinetic muscle test, and measurement of joint range of motion. − In weaned patients and those with prolonged weaning from mechanical ventilation and oxygen use, reconditioning interventions are indicated in order to improve the physical status and to correct the motor and cognitive effects of prolonged immobilization in the intensive care area [40][41][42][43][44][45][46][47][48]. − As the effect of muscle activity in infections related to viral agents is not known, exercises aiming [15] at a gradual load increase based on subjective symptoms are recommended to maintain a normal function.…”
Section: Generation Of Recommendations and Consensusmentioning
confidence: 99%
“…Furthermore, 673 patients were also excluded because of ICU readmission, the number of patients readmitted within 1 year and the mortality data are unclear. Therefore, the data represent the long-term outcome of ICU survivals and not patients who required ICU care.Secondly, in comparison with the 1-year mortality data from 2006 to 2011, the 5-year mortality data presented only a sample size as the study was performed on only 831 patients from 2006 to 2007.Thirdly, the authors did not report the impact of ICU length of stay, treatment modalities such as the length of mechanical ventilation weaning modalities, tracheostomy, presence of specialized weaning units [2], and renal replacement on survival. No data on the quality of life of survivors were mentioned, including transfer to long-term care facilities or receiving in-home mechanical ventilation during the follow-up period [3].…”
mentioning
confidence: 99%
“…Thirdly, the authors did not report the impact of ICU length of stay, treatment modalities such as the length of mechanical ventilation weaning modalities, tracheostomy, presence of specialized weaning units [2], and renal replacement on survival. No data on the quality of life of survivors were mentioned, including transfer to long-term care facilities or receiving in-home mechanical ventilation during the follow-up period [3].…”
mentioning
confidence: 99%